Минимизация мощности управления электромагнитных механизмов - Божко, А.Е. (Видавничий дім "Академперіодика" НАН України, 2007)
A solution of the problem on the determination of an algorithm of optimum control over electromagnetic mechanisms is given. The problem was solved by the method of moments with minimization of the integral functional of energy.